Growth of Graphene/h-BN Heterostructures on Recyclable Pt Foils by One-Batch Chemical Vapor Deposition. Issue 1 (December 2017) - Qian, Yongteng; Ngoc, Huynh; Kang, Dae
Abstract High-quality large-area graphene/h-BN vertical heterostructures are promising building blocks for many viable applications such as energy harvesting/conversion, electronics and optoelectronics. Here, we successfully grew high-quality large-area graphene/h-BN vertical heterostructures on Pt foils by one-batch low-pressure chemical vapor deposition (LPCVD). We obtained the high quality of about 200-µm-wide graphene/h-BN film having uniform layer thickness. Moreover, the obtained graphene/h-BN heterostructures exhibited field effect mobility of up to 7, 200 cm2 V−1 s−1 at room temperature. These results suggest that such graphene/h-BN heterostructures on recyclable Pt foils grown by LPCVD are promising for high-performance graphene-based electronics.